Stickeen - Muir, John; Nang Chan Yeema (New York, USA Scholastic Inc., 1999)
Surrounded by deep canyons of ice, John Muir and a little black dog named Stickeen had their most memorable adventures together.
Keywords: Juvenile Nonfiction